Reinventando o Ensino Médio em Minas Gerais: condição e formação docente - Rosana Cecilia Pereira (2016)
This work is the result of a research which had the objective of understanding teaching and its conditions on the Reinventing High School Project (RHS), instituted by the Secretary of the State of Education of Minas Gerais, as an educational policy for basic education, from 2012 to 2014. With the purpose of reflecting about the teachers role, including their skills and duties, this research follows a path which goes from its conception to its implementation inside the schools, heading to the teachers perceptions about its effectiveness on the classroom, and finally their expectations and analysis about the impact on not only the time it takes for them to teach something, but also on the time it takes for the students to fully grasp it. The investigation takes on a qualitative approach, involving two schools from the city of Belo Horizonte, which were strategically chosen for their past track record with the projects implementation. The methodology used contemplates documental and bibliographical research, guiding the debate around the condition of High School Education in the last few years. The analysis includes data collected from interviews, questionnaires and institutional publications, with authors Nóvoa (2012), Contreras (2002) and Tardif (2014) as basic references. The results raise consideration towards the necessity of legitimizing the teaching staff as a primordial body on the sustainment of educational projects, recognizing them as both subject and protagonist of their own continuous development. The recognition of teachers and students not as passive recipients, but as agents is what makes the reinvention of school itself possible. Another highlighted aspect is this researchers own place in this research and her own formation, after analyzing the issue of her own craft she managed to comprehend the complexity of the Educational System, from the establishment itself to the implementation of an educational program